Stand structure is more important for forest productivity stability than tree, understory plant and soil biota species diversity - Wang, Tao; Dong, Lingbo; Liu, Zhaogang (Frontiers in Forests and Global Change, 2024)
Introduction The stability of forest productivity is an important management goal in order to sustain ecosystem services for an expanding human population and in the face of global climate change. Evidence from theoretical, observational, and experimental studies has demonstrated that higher biodiversity promotes stability of forest productivity. However, the majority of these studies have focused solely on tree diversity and have neglected the potentially important role of understory plant and soil biodiversity. Methods In this study, we explain the effect of tree, understory woody and herbaceous plant, and soil biota (fauna, fungi, and bacteria) species diversity on forest productivity and its stability over time (2000–2020) across an area of Northeast China covering 145 million hectares. We explore the eight stand structure variables for stability of forest productivity and the relationship between productivity stability and tree, understory plant, and soil biota species diversity. Results Our results show no significant, direct impact of understory plant, soil fungi, and bacteria species diversity on the stability of the forest ecosystem. Tree species diversity indirectly affects productivity stability by directly influencing stand structure, whereas soil fauna species diversity indirectly influences stability through its relationship with tree species diversity. Stand structure is more important than tree and soil fauna species diversity for forest productivity stability. Specifically, increasing crown height (CH) from its minimum to maximum value leads to a substantial gain of 20.394 in forest productivity stability. In contrast, raising tree species diversity (α-Tree) and soil fauna species diversity (α-Fauna) from their minimum to maximum values results in a modest reduction of only 0.399 and 0.231 in forest productivity stability, respectively. Discussion To increase the stability of forest productivity in response to climate change, we should adjust the stand structure more in the process of management rather than just considering biodiversity. Overall, this study highlights the ecological risks associated with large-scale biotic homogenization under future climate change and management practices.